The Use of Personal Inarisk Media in Improving the Concept of Disaster Information Literacy in social Studies Learning - Nia Kurniawan; Eldi Mulyana; Slamet Nopharipaldi Rohman; Triani Widyanti; Tetep .; Asep Supriyatna; Yopi Nugraha (Institut Pendidikan Indonesia, 2020)
The purpose of this study is to determine the improvement of the concept of disaster information literacy using InaRisk Personal learning media in social studies learning. This research approach uses quantitative with quasi-experimental method with nonquivqlent control group design. The population of this research is the seventh grade students of SMP Negeri 1 Tarogong Kaler. The sample was taken by purposive sampling technique with class VII A as the experimental class and class VII B as the control class. Based on the results of statistical analysis, the Asymp.sig.2-tailed value is 0.000 and a is 0.05, which means 0.000 <0.05, then Ho is rejected. From these data it can be concluded that the value of Asymp.sig. of 0.000 < 0.05, then there is a significant increase or learning that uses InaRisk Personal learning media is effective to be applied. Overall, the ability of the concept of disaster information literacy affects the preparedness of students in dealing with disasters in the surrounding environment. the ability of the concept of disaster information literacy in the experimental class increased significantly in terms of seeking information, identifying information, evaluating information, and using information.